Evaluation and mitigation of the undesired effect of DC bias on inverter power transformer - Isumbingabo, Emma Francoise (Department of Electrical Engineering, 2014)
Inverters have traditionally been used mostly in standalone systems (non-grid connected), Uninterruptible Power Supplies (UPS) and, more recently, in distributed generated systems (DGs). DG systems are based on grid connected inverters and are increasingly being connected to utility grids to convert renewable energy sources to the utility grids. Such sources are likely to have a significant impact in the future in meeting the electricity demands of industry and domestic consumption. Common DGs utilize DC power sources such as fuel cells, batteries, photovoltaic (solar) power, and wind power. Most of power supplies in domestic and industries are AC power consumers and, for this reason, the DC power has to be converted to meet the requirement. Two main causes of DC current in inverter power transformer are: 1) Non-linearity and asymmetry in its switching mechanism which may result in undesired DC current at its input. This DC current introduced into an inverter transformer results in the transformer's magnetic flux distortion and in some cases magnetic saturation. This, in turn, results in asymmetrical primary currents in the transformer (inverter side). This is due to the non linear characteristics of the transformer magnetic flux. 2) The same effects can be produced by the connection of asymmetrical loads (e.g. asymmetrical rectifier) to the inverter output. The result in both cases is an asymmetrical magnetic flux in the transformer. This is manifested as even and odd current harmonics as well as an increase in the reactive power requirement from the inverter. vi To remedy this situation, it is, therefore, necessary to incorporate into the inverter's control system a mechanism of cancelling the DC magnetic motive force (mmf) that causes the magnetic flux distortion. This Thesis presents a method of introducing a DC voltage component in the inverter's voltage output so as to inject the necessary DC current into the primary side of the inverter's transformer so as to cancel the total DC mmf that the transformer is subjected to ( supply and load side). This project consists of three main parts namely: Modeling, Simulation and Laboratory Experiment. Activities undertaken under Modeling and Simulation were as follows: Determining the effects of DC current on a power transformer. Investigating the likely occurrence of saturation of the power transformer incorporated in inverter systems. Mitigating the effects that can be caused by the presence of a DC component in the windings of a power transformer. After understanding the literature on the subject of interest, MATLAB SIMULINK and MATLAB m-files were used to simulate the behavior of the power transformer under three situations : The transformer under linear load. The transformer subjected to asymmetrical loading. The inverter system that has a power transformer on its output were designed in MATLAB and used to simulate the situation for each case. To validate the theory and simulation results, experimental work was carried out as follows: vii Investigation of the effects that DC (current) injection can have on a 6 kVA power transformer. Investigation of the performance of a 6 kVA power transformer under linear loading. Investigation of the performance of a 6 kVA power transformer under non-linear loads. Investigation of the likely occurrence of DC offset in inverter system. Mitigation of the effect of DC bias on power transformer using extra windings. Mitigation of the effects of DC offset in power inverter transformer by using the second harmonic content of the primary current as a feedback signal. Results obtained showed a successful implementation of the proposed method. However limitations of the controller performances were experienced and will require future work. It was concluded that a total removal of the undesired effects of DC bias is achievable and that total removal of DC offset in power inverter transformer is possible if the limitations of the controller are overcome.